Analisis Tingkat Kesiapan Perguruan Tinggi dan Tingkat Kepuasan Pengguna dalam Implementasi E-Learning System Sebagai Dampak dari Pandemi Covid 19 - Rita Rahayu (Jurnal Inovasi Pendidikan Ekonomi (JIPE), 2020)
This study aims to analyze the level of readiness of higher education institutions in implementing e-learning during COVID-19 pandemic. In addition, this study also tries to analyze the level of satisfaction in using e-learning at higher education. This study applied a survey method by sending online questionnaires to lecturers at various universities in West Sumatra. 112 respondents participated in this study. Based on the data, it was found that the level of technological readiness and human resources readiness at universities in West Sumatra are in the ready category, but still need a little improvement. Meanwhile, the levels of readiness of innovation and self-development are categorized as unprepared, and need improvement. Furthermore, this study also shows that the level of satisfaction of e-learning users is still quite satisfied.